Physical education techears' knowledge about chronic diseases risk factors in a southern Brazilian city. DOI: 10.5007/1980-0037.2012v14n1p61 - Leandro Quadro Corrêa; Marilda Borges Neutzling; Thiago Terra Borges; Lúcio Kerber Canabarro; Airton José Rombaldi (Universidade Federal de Santa Catarina, 2012)
The improvement in population quality of life may be associated to the increase in the awareness about chronic diseases risk factors. The aim of the present study was to evaluate physical education teachers' knowledge about the associations between four behavioral factors (sedentary lifestyle, smoking, abusive alcohol intake, and inadequate eating) and eight diseases (diabetes, hypertension, AIDS, osteoporosis, lung cancer, depression, liver cirrhosis and acute myocardial infarction). A census-based cross-sectional study was carried out including 188 teachers (men and women) from public and private schools from Pelotas/RS. For each behavioral factor, a knowledge score was generated, ranging from zero to eight points. The highest score was observed for sedentary lifestyle (6.4), followed by inadequate eating (5.9), smoking (5.3), and abusive alcohol intake (4.5). Overall, higher knowledge scores were observed among teachers from lower age groups, and workplace and working hours were also associated to the outcome. Governmental strategies in health and education are needed to improve teacher's knowledge enabling professionals to perform their jobs satisfactory.